DEVELOPMENT OF CROSSWORD LEARNING MEDIA USING ECLIPSE CROSSWORD ON ADDITIVE AND ADDICTIVE SUBSTANCE MATERIAL IN CLASS VIII SMP/MTs - Damayanti, Rina Damayanti; Oktaffi Arinna Manasikana; Dyah Ayu Fajarianingtyas; Tita Tanjung (NUKLEO SAINS : JURNAL PENDIDIKAN IPA, 2025)
The aim of this research is to describe the process of developing crossword puzzle learning media using the eclipse crossword on additive and addictive substance material for class VIII SMP/MTs students. The media development procedure uses ADDIE which includes the Analyze, Design, Development, Implementation and Evaluation stages. This research also aims to determine the results of the validation of crossword puzzle learning media using the eclipse crossword on additive and addictive substance material for class VIII SMP/MTs students carried out by experts. After going through the validation stage, the final product is then described thoroughly. Obtaining research data using media validation sheets and material validation. The results of the research revealed that crossword puzzle media development using the eclipse crossword on additive and addictive substance material had gone through a validity test and received suggestions and input from three validators, namely two experts and one practitioner consistingof media experts, science material experts, and SMP/MTs science practitioner expert. The results of the assessment by media expert validators obtained an average score of 3.57 in the "Very Valid" category, with media validation obtained at 3.03, material validation at 4.10, and expert practitioners at 3.60. Tujuan penelitian ini adalah untuk mendeskripsikan proses pengembangan media pembelajaran teka teki silang menggunakan eclipse crossword pada materi zat aditif dan adiktif pada siswa kelas VIII SMP/MTs. Prosedur pengembangan media menggunakan ADDIE, yang meliputi tahapan Analyze, Design, Development, Implementation, and Evaluastion. Penelitian ini juga bertujuan untuk mengetahui hasil validasi para ahli terhadap media pembelajaran teka teki silang menggunakan eclipse crossword pada materi zat aditif dan adiktif siswa kelas VIII SMP/MTs. Setelah melalui tahap validasi, produk akhir dari pengembangan ini selanjutnya dideskripsikan secara menyeluruh. Data diperoleh dengan menggunakan lembar validasi media dan validasi materi. Hasil penelitian menunjukkan bahwa pengembangan media pembelajaran teka-teki silang menggunakan elipse crossword pada materi zat aditif dan adiktif telah melalui uji validitas dan mendapat saran serta masukandari tiga validator, yakni dua dosen dan satu guru IPA MTs Nurul Iman Jombang. Hasil penilaian oleh validator media pembelajaran teka teki silang menggunakan eclipse crossword pada materi zat aditif dan adiktif memperoleh skor rata rata sebesar (3,03) dan validator materi (4,10) serta rata-rata skor sebesar (3,57) dengan kategori “Sangat Valid”.